Overcoming the psychological barriers to energy conservation behaviour: The influence of objective and subjective environmental knowledge - Dursun, İnci; Kabadayi, Ebru Tumer; Tuger, Ahmet Tugrul (Wiley, 2019)
Energy conservation is a crucial aspect of responsible consumption which is the reflection of individual efforts for sustainability. However, especially young consumers are reluctant to reduce their energy consumption despite their pro-environmental attitudes. Resistance to behavioural change can be attributed to various psychological barriers that help consumer to avoid engaging in pro-environmental actions. In this context, the first aim of the study is to extend the theoretical and empirical evidence regarding impeding effects of psychological barriers on individual energy conservation behaviour. Secondly, the study investigates the alleviating role of environmental knowledge on those barriers that limit energy conservation. Proposed impeding effects of objective and subjective environmental knowledge on various denial mechanisms, which are in turn expected to hinder energy conservation, were tested using the survey data collected from young Turkish consumers. Results suggest that denial mechanisms hinder young consumers' energy conservation behaviour indirectly through diminishing feelings of moral obligations. Moreover, it was found that objective environmental knowledge's effect can be used to break down the psychological barriers and to facilitate the change towards more sustainable energy consumption patterns. Implications of the findings and directions for future research are discussed.
Keywords: denial mechanisms; energy conservation; environmental knowledge; personal norms